Evaluating the Role of Investment Production and Linkage Capability in Improving the Performance of MSMEs - Singh, Navdeep (My University, 2012)
ABSTRACT Technology is recognized as one of the most valuable resources that provide sustainable competitive advantages. Technical advancement is a key driving force and an important source of economic and social development. In addition, technology has become the center of competition in the world market. The diffusion, assimilation and further improvement of new technology determine the patterns of competition, growth and trade around the world at large. The capability of accessing new technology thus affects the ability of companies in emerging countries to build indigenous technological capabilities and compete in world markets. Accordingly, technological capability (TC) has become the focus of attention not only among academicians, but also among entrepreneurs of manufacturing organizations. Industrial development is recognized as a process of acquiring technological capabilities and transforming them into product and process innovations in the course of continuous technological change. In other words, the process of industrial development, in fact, is the process of generating technological capabilities. Therefore, technological capabilities play a strategic role in affecting the competitive advantage of a company, an industry, and even a country. Technological capability has become a pervasive factor of production in the future. Thus, the development of technological capabilities is critical for companies, especially those manufacturing companies in the countries which are in a catch-up phase of industrialization. The objective of the present work is to analyze the technology innovation capabilities of small scale manufacturing industry especially the cutting tool and machine tool industry in the state of Punjab. The issues explored include, present status and future scope of technology innovation capabilities of small scale manufacturing industry regarding investment capability, production capability and linkage capability, reasons for low performance in the area of firm performance include innovation performance, sales performance and product performance etc. The present report is subdivided into five main chapters. The first chapter gives introduction about SMEs, technology capability and the need for enhancing technology capability of the organizations. The second chapter brings together the extensive literature regarding the various factors influencing the technology capability of the organizations and the various gaps in the present literature. Third chapter puts forward the methodology to be adopted for carrying out the future research, fourth chapter presents the findings of survey based results, the results obtained ix after quantitative analysis of survey data. Analysis of three input variables viz. investment capability, production capability and linkage capability with respect to output variables viz. innovation performance, sales performance and product performance has been performed using correlation and regression analysis. Principal component analysis has been done to reduce the issues under each input factor. Last and final chapter presents the conclusion work and also the scope of future work.